THE INFLUENCE OF FAMILY HABITS ON CHILDREN'S IMMUNE RESISTANCE (International journal of medical sciences, 2026)
This review article examines the influence of family habits and lifestyle on the development of immune resistance in children from the perspective of medical prevention and social hygiene. The article analyzes data from modern studies on the role of nutrition, sleep patterns, physical activity levels, hygiene skills, the psycho-emotional climate in the family, as well as parental behavioral factors (smoking, alcohol consumption, attitudes toward vaccination) in the development of a child's immune system. It is shown that the family environment is a key modifiable factor determining the incidence of infectious diseases, adaptive capacity, and overall health of children. Particular attention is paid to early childhood as a critical period of immune programming. The importance of preventive measures aimed at developing healthy family habits is emphasized as the basis for strengthening immunity and reducing disease incidence in the child population.